Temperature-associated effects on methanogenesis and microbial reductive dechlorination of trichloroethene in contaminated aquifer sediments - Bin Hudari, Mohammad Sufian; Deb, Sushmita; Vogt, Carsten; Filippini, Maria; Nijenhuis, Ivonne (Frontiers in Water, 2025)
BackgroundAquifer thermal energy storage (ATES) is a subsurface technology for urban heating and cooling. However, ATES systems may intersect with legacy groundwater contaminants from past anthropogenic activities. Chlorinated ethenes, particularly tetrachloroethene (PCE) and trichloroethene (TCE), are common pollutants that can undergo microbial reductive dechlorination to cis-dichloroethene (cis-DCE), vinyl chloride (VC), and ultimately ethene. Since microbial activity is temperature dependent, heat storage in ATES systems may influence dechlorination efficiency.MethodsThe study assessed the effect of temperature on microbial reductive dechlorination and community composition using sediment from a contaminated aquifer in Ferrara, Italy, where VC accumulation is of concern. Laboratory microcosms were amended with TCE and lactate, incubated at 10–60°C, and monitored for 105 days.ResultsComplete dechlorination to ethene occurred at 10–20°C and was linked to Dehalogenimonas spp. cis-DCE and VC accumulated at 30°C and 40°C, respectively, while no dechlorination activity was observed at 50°C and 60°C, suggesting temperature-related inhibition. Methanogenesis occurred between 10 and 40°C and was associated with Methanosarcina, Methanothrix (mainly in non-TCE-amended controls), and Methanomicrobia (10–30°C). Methanogenic activity was absent above 40°C and delayed at 10°C.ConclusionThese results suggest that microbial dechlorination of chlorinated ethenes is impaired at temperatures exceeding 40°C. Therefore, integrating low- or medium-temperature (< 40°C) ATES with enhanced natural attenuation may offer a viable strategy for simultaneous energy storage and bioremediation in chlorinated solvent-contaminated aquifers.